2012
DOI: 10.2466/15.03.10.pms.115.5.512-520
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability Study for Standing Functional Reach Test Using Modified and Traditional Rulers

Abstract: The purposes of the study were (1) to estimate the standing reach distance, test-retest, and interrater reliability of the functional reach test using traditional and modified rulers and (2) to evaluate the difference in the scores based on one trial, the mean of two or of three trials. Sixty-four individuals (M age = 36.3 yr., SD = 19.5, range = 19 to 70 years; 24 men, 40 women) volunteered to participate. Differences in measurements were examined. The intraclass correlation coefficient (ICC) was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Furthermore, the inter-rater reliability of the HSEBT was high, with ICC values ranging from 0.90 to 0.98. FR inter-rater ICC values between 0.73 and 0.98 have been reported [22,27,28], while SEBT values range from 0.81 to 0.93 [21,24,26,29]. Even though our ICC results showed high HSEBT inter-rater reliability, the repeated measure ANOVA results suggested that in five of the 20 tests at least one rater differed systematically from the other raters ( Table 2).…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…Furthermore, the inter-rater reliability of the HSEBT was high, with ICC values ranging from 0.90 to 0.98. FR inter-rater ICC values between 0.73 and 0.98 have been reported [22,27,28], while SEBT values range from 0.81 to 0.93 [21,24,26,29]. Even though our ICC results showed high HSEBT inter-rater reliability, the repeated measure ANOVA results suggested that in five of the 20 tests at least one rater differed systematically from the other raters ( Table 2).…”
Section: Discussionmentioning
confidence: 44%
“…The SEM values reported for the SEBT range from 2.2 to 4.8 cm and 2.0 to 5.0 cm for test-retest and inter-rater reliability, respectively [21,23,30], while FR ranged from 2.1 to 4.0 cm and 2.1 to 4.3 cm for inter-rater and test-retest reliability, respectively [22]. In summary, the SEM values found for HSEBT are comparable or lower than those established for the SEBT and FR.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…17 It is reliable and easy to perform. 17,18 A study also showed excellent correlation between Berg Balance Scale and functional reach distance. 19 However, previous research has shown that functional reach distance is not well correlated with COG excursion, 20 implying that functional reach may not serve as a good gauge of dynamic balance.…”
Section: Introductionmentioning
confidence: 85%